Beyond Conventional Approaches: The Revolutionary Role of Nanoparticles in Breast Cancer - Mohan Liu; Yusi Wang; Yan Li; Yibing Zhang; Bailing Zhou; Lei Yang; Xi Yan; Li Yang (MedComm – Biomaterials and Applications)
ABSTRACT Breast cancer (BCa) remains a significant health challenge worldwide, with a high propensity for early metastasis and poor prognosis. While surgery, chemotherapy, and radiotherapy are fundamental for managing BCa, severe side effects, such as low patient adherence and suboptimal survival outcomes, cause concern. Therefore, there is a critical need to innovate new approaches that facilitate early detection, accurate diagnosis, and more effective treatment strategies for BCa. Nanotechnological approaches have been introduced for the diagnosis and treatment of various cancers, especially BCa. The current review aims to emphasize and highlight possible applications of nanomedicine in early detection, accurate diagnosis and efficient treatment strategies for BCa. Nanocarriers can deliver chemotherapeutic agents, enhancing cytotoxicity against BCa cells and preventing the development of drug resistance. Nanoparticles also boost the efficacy of gene therapy which promotes their potential for regulating gene expression. The co‐delivery of drugs and genes by nanoparticles can have a synergistic effect on BCa and remodel the tumor microenvironment. In this review, we discussed the latest advances in the application of nanomedicines for diagnosing and treating BCa. Current research highlights the potential benefits of nanomedicine over traditional approaches and further efforts to translate these research findings into clinical practice for BCa.